2003
DOI: 10.4315/0362-028x-66.6.1025
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation by Ionizing Radiation of Salmonella Enteritidis, Salmonella Infantis, and Vibrio parahaemolyticus in Oysters (Crassostrea brasiliana)

Abstract: Irradiation is considered one of the most efficient technological processes for the reduction of microorganisms in food. It can be used to improve the safety of food products, and to extend their shelf lives. Oysters are considered one of the most important vehicles for pathogenic bacteria because of their feeding characteristics. The aim of this study was to evaluate the influence of a gamma radiation process on high levels of Salmonella Enteritidis, Salmonella Infantis, and Vibrio parahaemolyticus incorporat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
39
0
4

Year Published

2009
2009
2017
2017

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(47 citation statements)
references
References 18 publications
4
39
0
4
Order By: Relevance
“…Inactivation studies on Salmonella spp. with live oysters showed a relatively low D 10 value of 0.45 to 0.55 kGy (16). Harewood et al (12) reported that virus inactivation required a higher dose of irradiation than bacterial pathogens.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Inactivation studies on Salmonella spp. with live oysters showed a relatively low D 10 value of 0.45 to 0.55 kGy (16). Harewood et al (12) reported that virus inactivation required a higher dose of irradiation than bacterial pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…However, to determine the dose required for complete inactivation of the viruses in the oyster meat, higher E-beam doses were utilized. Gamma radiation as a sanitization treatment for shellfish has been studied by different research groups (12,16,(25)(26)(27)(28). A variety of bacterial pathogens are susceptible to ionizing radiation, such as Vibrio cholerae, V. parahaemolyticus, and V. vulnificus, with D 10 values as low as 0.1 kGy (27,29).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other postharvest processing methods include use of high hydrostatic pressure [69], use of supercritical carbondioxide [70], and inactivation of zoonotic bacteria, including Salmonella and Vibrio spp. by ionizing radiation [71]. One study described X-ray inactivation of V. parahaemolyticus and inherent microflora in oysters to less than detectable limit [72].…”
Section: Strategies To Reduce Zoonotic Bacteria In Oystersmentioning
confidence: 99%
“…Jakabi et al [68] studied the survival of S. enteritidis and S. infantis inoculated into oysters and sensory properties as the result of irradiation with doses in the dose range of 0.5-3.0 kGy. The number of those both Salmonella populations decreased after a 3.0 kGy dose by five to six logs.…”
Section: Reducing Salmonella Spp In Fish and Shellfishmentioning
confidence: 99%